MODEL PEMBELAJARAN DISCOVERY LEARNING PADA OPERASI BILANGAN KELAS 4 SD - INDAH, NUR LULUK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The goal of developing and implementing this model is to improve students' understanding of number operation concepts as well as their critical thinking skills. With Discovery Learning, it is hoped that students can learn independently and develop logical thinking abilities, while also increasing their interest in learning mathematics. The implementation procedure of this model involves stages that include orientation or problem identification, hypothesis formulation, data collection, verification or proof, and drawing conclusions. At the orientation stage, the teacher introduces problems related to number operations that need to be solved. Students are then invited to formulate hypotheses regarding possible solutions. Next, they collect relevant data or information through exploration activities facilitated by the teacher. At the verification stage, students test the hypotheses they made earlier. Finally, students are invited to draw conclusions based on the analysis of the learning process that has been conducted. The results of implementing the Discovery Learning model on number operations in 4th grade elementary school show an improvement in students' understanding of basic number operation concepts, such as addition, subtraction, multiplication, and division. In addition, this model successfully improved students' critical thinking skills and problem-solving abilities. Most students also showed an increase in motivation and enthusiasm in learning mathematics. In conclusion, the Discovery Learning Model has proven effective in enhancing students' conceptual understanding and critical thinking skills in number operations in 4th-grade elementary school. The follow-up to the implementation of this model is to make further adjustments so that this method can be applied to various other mathematics materials, as well as to strengthen teacher guidance in the process of concept discovery by students to optimize learning outcomes. ABSTRAKTujuan pengembangan dan penerapan model ini adalah untuk meningkatkan pemahaman konsep operasi bilangan serta keterampilan berpikir kritis siswa. Dengan Discovery Learning, diharapkan siswa dapat belajar secara mandiri dan mengembangkan kemampuan berpikir logis, sekaligus meningkatkan minat belajar mereka terhadap matematika. Prosedur pelaksanaan model ini melibatkan tahapan-tahapan yang meliputi orientasi atau pengenalan masalah, formulasi hipotesis, pengumpulan data, verifikasi atau pembuktian, dan menarik kesimpulan. Pada tahap orientasi, guru memperkenalkan masalah terkait operasi bilangan yang harus diselesaikan. Siswa kemudian diajak untuk merumuskan hipotesis mengenai solusi yang mungkin. Selanjutnya, mereka mengumpulkan data atau informasi yang relevan melalui kegiatan eksplorasi yang difasilitasi oleh guru. Pada tahap verifikasi, siswa menguji hipotesis yang mereka buat sebelumnya. Terakhir, siswa diajak menarik kesimpulan berdasarkan hasil analisis terhadap proses pembelajaran yang telah dilakukan. Hasil pelaksanaan model Discovery Learning pada operasi bilangan di kelas 4 SD menunjukkan peningkatan pemahaman siswa terhadap konsep operasi bilangan dasar, seperti penjumlahan, pengurangan, perkalian, dan pembagian. Selain itu, model ini berhasil meningkatkan keterampilan berpikir kritis dan kemampuan siswa dalam memecahkan masalah. Sebagian besar siswa juga menunjukkan peningkatan motivasi dan antusiasme dalam belajar matematika. Kesimpulannya, Model Pembelajaran Discovery Learning terbukti efektif dalam meningkatkan pemahaman konsep dan keterampilan berpikir kritis siswa pada operasi bilangan di kelas 4 SD. Tindak lanjut dari penerapan model ini adalah melakukan penyesuaian lebih lanjut agar metode ini dapat diterapkan pada berbagai materi matematika lainnya, serta memperkuat pendampingan guru dalam proses penemuan konsep oleh siswa agar hasil belajar semakin optimal.